Petrosaltator gen. nov., a new genus replacement for the North African sengi Elephantulus rozeti (Macroscelidea; Macroscelididae) - Dumbacher, John P. (Zootaxa, 2016)
In 2003, a molecular phylogeny was published that examined the role of the Sahara Desert as a vicariant event in the evolution of sengis (also known as elephant-shrews.) The phylogeny included a single sample from the North African sengi, Elephantulus rozeti (Duvernoy, 1833), which was found to be more closely related to the sengi genus Petrodromus Peters, 1846 than to other Elephantulus. Here we independently test the monophyly of Elephantulus using an additional specimen of E. rozeti and similar phylogenetic analyses, and discuss additional morphological and behavioral data that support the phylogeny. We propose a revised taxonomy that reflects the current paraphyly of Elephantulus and the sister relationship of E. rozeti and Petrodromus, including a new genus name for the North African sengi, Petrosaltator rozeti gen. nov., nov. comb. We additionally define two tribes within the subfamily Macroscelidinae, the Macroscelidini (including Macroscelides, Petrodromus, and Petrosaltator), and the Elephantulini (including all other members of Elephantulus).